Study on the Implementation of the Green City Development Program (PK2H) through Optimizing Green Open Space (RTH) in Ilir Barat I District, Palembang City - Yuli Rosianty; Efendi Agus Waluyo; Rendi Gunawan (Universitas Muhammadiyah Palembang, 2021)
This study aims to analyze the development, utilization, supervision, and control of the green open space program in Ilir Barat I Sub-District, Palembang. This study was conducted in, Ilir Barat I Sub-District, Palembang city.October 2019 to December 2019. On this research used descriptive qualitative methods and analysis of vegetation (Anveg) by using and purposive sampling. Based on the analysis,The Sub-District of Ilir Barat I has a Green Open Space (RTH) covering an area of 101,389 m2 with a percentage of 0.51%. The area of it does not meet the minimum area of green space based on Law No. 26 of 2007 in article 29 paragraph (2) of 30% and has met the requirements of article 29 paragraph (3) of 20%. With the distribution of green open space is the Puncak Sekuning TPU with an area of 40,000 m² with a percentage of 0.20%.The green space location with the smallest area in the stadium of Bumi Sriwijaya has a green space of 1,627 m² with a percentage of 0.01%. The area of green space in the District of Ilir Barat I Palembang based on the results of the study was 101,389 m², while the area of it based on Palembang PRKP data in the Sub-District of Ilir Barat I of Palembang City was 96,166 m². Researcher measurement data has a difference of 5,223 m² with data from the Palembang City PRKP Service. Angsana tree (Pterocarpus indicus), The highest number of tree in green line (road side) is Trembesi (Albizia saman) while in median road is Tanjung (Mimusops elengi).